(untitled) (Web of Teachers: Inderscience Research, 2025)
The article examines the formation of the first sports societies in Turkestan at the end of the 19th and the beginning of the 20th centuries and their role in socio-political life. During this period, at the initiative of the intelligentsia, sports clubs and societies began to emerge in cities such as Tashkent, Samarkand, and Andijan. Cycling, tennis, weightlifting, wrestling, and football gained popularity among the local population. The establishment of the Tashkent Amateur Cycling Society in 1894, followed by the creation of tennis courts, gymnastics, and athletics groups, marked significant steps in the development of sports. Sports societies not only promoted physical culture but also played a crucial role in fostering national identity, social integration, and educational activities. The achievements of local wrestlers, such as Ahmad Polvon, in international competitions bolstered national pride. The article analyzes the influence of European culture, foreign experiences, and socio-political changes through the lens of sports. This study is a valuable resource for researchers exploring the history of sports, social transformations, and national movements.